2004
DOI: 10.1002/masy.200450230
|View full text |Cite
|
Sign up to set email alerts
|

New routes to high solid content latexes: a process for in situ particle nucleation and growth

Abstract: A means of generating latices with solid contents well over 70% (v/v) without the use of intermediate seeds is proposed. It is demonstrated that the use of an electrically neutral initiation system (hydrogen peroxide) in the initial stages of the process, followed by an initiator yielding negatively charged free radicals (ammonium persulphate) changes the way in which the system generates stable particles. The reason for this change is the need to avoid stabilising small, homogeneously nucleated particles duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
0
15
0
3
Order By: Relevance
“…Recently, many research groups have obtained HSC latex, including Greenwood [31,32], Ai [7,8], Chu [42][43][44][45], Schneider [56][57][58], Salima Boutti [53][54][55], Leiza [66], do Amaral [68][69][70], Wei [73] and Zhang et al [76][77][78][79][80][81]. Generally speaking, most HSC latexes were prepared by using the following four methods: conventional emulsion polymerization, miniemulsion polymerization, self-emulsification polymerization, and concentrated emulsion polymerization.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…Recently, many research groups have obtained HSC latex, including Greenwood [31,32], Ai [7,8], Chu [42][43][44][45], Schneider [56][57][58], Salima Boutti [53][54][55], Leiza [66], do Amaral [68][69][70], Wei [73] and Zhang et al [76][77][78][79][80][81]. Generally speaking, most HSC latexes were prepared by using the following four methods: conventional emulsion polymerization, miniemulsion polymerization, self-emulsification polymerization, and concentrated emulsion polymerization.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…However, formulation of these dispersions typically requires a well-defined particle size distribution (PSD) in order to maintain both colloidal stability and an acceptable product viscosity [3]. A number of recently published results have shown that it is possible to produce low-viscosity latexes with solid loadings above 70 vol.-% if the PSD is wellengineered [4,5]; typically, the target PSD will be broad and bimodal, with the small particles designed to fit in the interstices created by the large particle lattice.…”
Section: Introductionmentioning
confidence: 99%
“…This has been discussed in a number of articles, and the reader is referred to Refs. 12 and 13 for a more detailed discussion. Different attempts have been made to synthesize controlled particle size and/or high solid core shell particles.…”
Section: Introductionmentioning
confidence: 99%
“…In many occasions high solid content latexes have been made by creating a bimodal particle size distribution 7,8 and/or by using larger average particle sizes. 1,[8][9][10][11][12] However, in the specific case of an impact modifying core-shell polymer neither of these options is permissible since one needs a latex with small, well-defined particles in order to obtain acceptable impact properties, so one needs to work with monomodal systems. In addition there will be an upper limit of operability and on product quality set by the viscosity.…”
Section: Introductionmentioning
confidence: 99%